STATISTICAL GEOGRAPHY. Problems in Analyzing Areal Data. (Sociology & Social Research, 1962)
Reviews the book "Statistical Geography: Problems in Analyzing Areal Data," by Otis Dudley Duncan, R. P. Cuzzort and Beverly Duncan.